Strategi Kreatif Iklan Chitato Lite Versi Lite Man VS Monster Kentang di Youtube - Andes Yushar Zulfikar; Agustrijanto Agustrijanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2026)
The tokusatsu style can be used as a creative strategy in advertising production. The combination of tokusatsu elements with retro visuals and the delivery of advertising messages through humor can be an attractive feature for advertisements. This is evident in the Chitato Lite Aburi Seaweed commercial titled “Lite Man Vs Monster Kentang.” This study applies Suyanto's concept of creative strategy, which includes appeals such as humor and music, along with execution styles like slice of life, demonstration, animation, fantasy, and dramatization. The aim of this study is to explore the creative strategy employed by the advertiser in producing the commercial. A qualitative descriptive approach with a case study method was used to analyze the strategy. The researcher conducted interviews with the production team from Popcult Group, the advertising agency behind the commercial. The results show that the Ultraman series was used as a reference due to its familiarity among the target audience. This aligns with the product’s tagline: “Japanese potato chips not sold in Japan.”